New business models with Industrie 4.0 in the German Mittelstand. (9th April 2021) - Kraft, Patricia; Helm, Roland; Dowling, Michael
Medium-sized enterprises called the 'Mittelstand' are an important pillar of the German economy. However, these firms have not been as quick to develop new digital business models that characterise a shift to digital manufacturing, which is called 'Industrie 4.0' or the Industrial Internet of Things (IIoT) in Germany. In this paper, we analyse different types of digital business models, including important external drivers (technology, security, and standards) and internal drivers (business processes, organisation forms, inter-firm cooperation, and human resources strategies). We show that the complexity and the chances of success of new business models with Industrie 4.0 increase with the integration of players from the respective ecosystem and a focus on the system rather than the product. To illustrate such business models in detail, we analyse a German 'Mittelstand' manufacturer that is currently implementing Industrie 4.0.